Expanding pneumatocele in an ELBW infant - Theresa R. Price; Mechelle A. Miller; Alicia C. Prescott; Jeffery M. Meadows; Benjamin D. Tabak (Elsevier, 2021)
Pneumatoceles are gas-filled cysts that can develop within lung parenchyma, often as the result of barotrauma. Pneumatoceles in extremely low birth weight (ELBW) premature infants present unique challenges, particularly when conservative management fails. We present a case of an enlarging pneumatocele that resulted in severe hemodynamic compromise which required surgical intervention. We review the described interventional techniques for pneumatocele management in the EBLW population and their indications.